2021
DOI: 10.1097/md.0000000000026627
|View full text |Cite
|
Sign up to set email alerts
|

Exploring diagnostic and prognostic predictive values of microRNAs for acute myocardial infarction

Abstract: Objective: Previous investigations yielded inconsistent results for diagnostic and prognostic predictive values of MicroRNAs (miRNAs) for acute myocardial infarction (AMI).Methods and results: We systematically searched on PubMed and Web of Science for articles explored association of miRNAs and AMI published from January 1989 to March 2019. For diagnostic studies, a summary of sensitivity, specificity, positive likelihood ratios (PLR), negative likelihood ratios (NLR), and diagnostic odds ratio (DOR), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Release kinetics of circulating miRNA-208a were also observed in early phases of MI, the peak being registered at 3 h after reperfusion (p < 0.001), while traditional biomarkers such as cTnI and CK-MBmass reached the maximum concentrations at 6 h after reperfusion [101]. Moreover, peak values of miRNA-208b were well associated with the ejection fraction and troponin I levels [102], and a recent meta-analysis identified a significant association between miR-208 and mortality after AMI (HR 1.09, 95% CI 1.01--1.18) [103]. Cheng et al [104] found that urine concentration of miRNA-1 was raised and peaked at 24 h in rat model, and in STEMI patients, 60% of them had increased levels, whereas urine miRNA-208 can be found in only 25% of patients, suggesting that urine miRNA-208 might not be an applicable biomarker.…”
Section: Mirna-208mentioning
confidence: 99%
See 1 more Smart Citation
“…Release kinetics of circulating miRNA-208a were also observed in early phases of MI, the peak being registered at 3 h after reperfusion (p < 0.001), while traditional biomarkers such as cTnI and CK-MBmass reached the maximum concentrations at 6 h after reperfusion [101]. Moreover, peak values of miRNA-208b were well associated with the ejection fraction and troponin I levels [102], and a recent meta-analysis identified a significant association between miR-208 and mortality after AMI (HR 1.09, 95% CI 1.01--1.18) [103]. Cheng et al [104] found that urine concentration of miRNA-1 was raised and peaked at 24 h in rat model, and in STEMI patients, 60% of them had increased levels, whereas urine miRNA-208 can be found in only 25% of patients, suggesting that urine miRNA-208 might not be an applicable biomarker.…”
Section: Mirna-208mentioning
confidence: 99%
“…Knockdown of miR-499 persuaded myocardial apoptosis and elevated the infarct size [136]. Increased levels of miR-449a are correlated with AMI in rodent models and in humans [137], especially in the first days, followed by a decline to undetectable levels and with a sensitivity (0.84 (95% CI: 0.70-0.92)) and specificity (0.97 (95% CI: 0.87-0.99)) in AMI detection [103]. Upon evaluating patients with stable CAD and STEMI vs. control, authors found after adjustment for risk factors elevated miR499-5p levels and pointed out its role as an independent predictor of STEMI [138].…”
Section: Mirna-449amentioning
confidence: 99%
“…A recent meta-analysis that included 13 studies evaluated the diagnostic value of miRNA-208, and reported the performance of pooled miR-208 (a/b) sensitivity and specificity at 0.83 (95% CI: 0.74-0.89) and 0.98 (95% CI: 0.88-0.99), respectively, and SROC 0.94 (95% CI: 0.91-0.95), albeit with a significant potential for publication bias [31]. There appears to be a significant association between elevated miR-208 levels and higher mortality in AMI, compared to other myomiRs [34,35].…”
Section: Mir-208mentioning
confidence: 99%
“…Myocardial infarction (MI) is a common cardiovascular disease that causes irreversible damage to the myocardium due to hypoxia 23 , 4,16 .It has been shown that MI is one of the most common causes of morbidity and death in the world, and more than one-third of deaths in developed countries are caused by MI each year 12,32 . At present, the main clinical therapy for coronary heart disease is thrombolysis and surgical therapy 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al 5 examined the plasma exosomal miRNA pro les of 118 subjects and identi ed 18 speci c miRNAs that may act as potential biomarkers for early MI detection. A recent meta-analysis suggested that circulating miR-1, miR-133, miR-208, and miR-499 showed diagnostic value, while miR-208 showed prognostic predictive value for MI 12 . These studies show that exosomal mRNAs can be used as a potential diagnostic marker for MI.…”
Section: Introductionmentioning
confidence: 99%